Secondary electrons as an energy source for life - Stelmach, Kamil; Neveu, Marc; Vick-Majors, Trista J.; Mickol, Rebecca L.; Chou, Luoth; Webster, Kevin D.; Tilley, Matt; Zacchei, Federica; Escudero, Cristina; Flores Martinez, Claudio; Labrado, Amanda; Fernández, Enrique J.G. (Astrobiology, 2018)
Life on Earth is found in a wide range of environments as long as the basic requirements of a liquid solvent, a nutrient source, and free energy are met. Previous hypotheses have speculated how extraterrestrial microbial life may function, among them that particle radiation might power living cells indirectly through radiolytic products. On Earth, so-called electrophilic organisms can harness electron flow from an extracellular cathode to build biomolecules. Here, we describe two hypothetical mechanisms, termed “direct electrophy” and “indirect electrophy” or “fluorosynthesis,” by which organisms could harness extracellular free electrons to synthesize organic matter, thus expanding the ensemble of potential habitats in which extraterrestrial organisms might be found in the Solar System and beyond. The first mechanism involves the direct flow of secondary electrons from particle radiation to a microbial cell to power the organism. The second involves the indirect utilization of impinging secondary electrons and a fluorescing molecule, either biotic or abiotic in origin, to drive photosynthesis. Both mechanisms involve the attenuation of an incoming particle's energy to create low-energy secondary electrons. The validity of the hypotheses is assessed through simple calculations showing the biomass density attainable from the energy supplied. Also discussed are potential survival strategies that could be used by organisms living in possible habitats with a plentiful supply of secondary electrons, such as near the surface of an icy moon. While we acknowledge that the only definitive test for the hypothesis is to collect specimens, we also describe experiments or terrestrial observations that could support or nullify the hypotheses. Key Words: Radiation Electrophiles Subsurface life. Astrobiology 18, 73-85.
Gesehen am 14.04.2020